1985
DOI: 10.1070/qe1985v015n04abeh007007
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the gain of an ultraviolet nitrogen laser

Abstract: Dense (Bi, Pb), Sr,Ca,Cu,O, bars were fabricated by sinter forging. The bars were highly phase-pure and exhibited strong textures in which t h e c axes of the platelike grains were preferentially aligned parallel to the pressing direction. Transport critical current densities increased with texture, reaching a maximum of 8 x io3 A cm-2 at 77 K in a seif-field. Optimal processing in air occurred at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(21) and (22), N gas is the ground-state gas density; r C and r B are the electron impact cross-sections of the N 2 (C) and N 2 (B) states, respectively; gðT e ; vÞ is the normalized Maxwell-Boltzmann distribution; r stim is the stimulated emission cross-section and is given by k 2 =8pDms C % 4:5 Â 10 À15 cm 2 for Dm ¼ 278 GHz [23]; s C and s B (40 ns and 6 ls, respectively) are the spontaneous lifetime of the C and B laser levels; s ph represents the mean cavity lifetime; c is the geometrical factor for spontaneous emission; and V dis ¼ sd AMP l AMP is the discharge volume.…”
Section: Rate Equationsmentioning
confidence: 99%
“…(21) and (22), N gas is the ground-state gas density; r C and r B are the electron impact cross-sections of the N 2 (C) and N 2 (B) states, respectively; gðT e ; vÞ is the normalized Maxwell-Boltzmann distribution; r stim is the stimulated emission cross-section and is given by k 2 =8pDms C % 4:5 Â 10 À15 cm 2 for Dm ¼ 278 GHz [23]; s C and s B (40 ns and 6 ls, respectively) are the spontaneous lifetime of the C and B laser levels; s ph represents the mean cavity lifetime; c is the geometrical factor for spontaneous emission; and V dis ¼ sd AMP l AMP is the discharge volume.…”
Section: Rate Equationsmentioning
confidence: 99%
“…is Einstein's coefficient for stimulated emission, λ and ν are the lasing wavelength and frequency, c is the speed of light, τ s is the spontaneous emission decay time and Δν is the line width for a collisionally broadened spectral line of the C-B transition (we use Δν = 0.1 nm for normal pressure, as measured in [34], and scale this value proportionally to pressure). The second summand on the right side is a spontaneous emission source.…”
Section: Model For a Single-pass Nitrogen Lasermentioning
confidence: 99%
“…9 In TE N 2 lasers, with just two exceptions, 3,4 it was found that the plot of g 0 parameter versus the discharge length is following a characteristic curve. 7 In all the measurements that have been reported so far, the laser electrodes have been fixed at some constant values, and in some studies with oscillator-amplifier ͑OSC-AMP͒ configurations, the laser systems were made to operate either at an atmospheric gas pressure, p AMP , of 760 Torr for the AMP, 6 or at most the laser was operating at two different AMP gas pressures, where it resulted in ⌬g 0 / ⌬p AMP = −9.5 ϫ 10 −4 cm −1 Torr −1 , and ⌬E s / ⌬p AMP = 1.63 J cm −2 Torr −1 . 9 There are only two reports where special attention has been paid for the TE-N 2 laser behavioral characteristics.…”
Section: Introductionmentioning
confidence: 99%